Determination of Customer Satisfaction of Bank Muamalat Palembang Branch Office - Nuri Fingkel; Nilawati Nilawati; Muhammadinah Muhammadinah; M Iqbal (Universitas Bangka Belitung, 2023)
The purpose of this study was to determine the effect of service quality, trust and excellent service on customer satisfaction at Bank Muamalat Palembang Branch Office. The study population was 48,783 customers of Bank Muamalat Palembang Branch Office, using the slovin formula, a sample of 100 people was obtained. Data collection using questionnaires distributed to respondents regarding service quality, trust, excellent service and customer satisfaction. The data analysis technique uses liner regression with hypothesis testing using the t test. The results showed that service quality affects customer satisfaction with a significance value of 0.017 <0.05. Trust affects customer satisfaction with a significance value of 0.019 <0.05 and excellent service affects customer satisfaction with a significance value of 0.007 <0.05. The results of this study can be concluded that all independent variables in this study include service quality, trust and excellent service affect customer satisfaction. It is hoped that the results of this study can be taken into consideration in order to make decisions regarding increasing customer satisfaction.